Risk factors of persistent diarrhea in children below 5 years of age - Baidya, Madhabi; Mahmud, Salauddin; Ghosh, Uzzal Kumar; Begum, Dilruba; Ahmed, Syed Shafi (Northern International Medical College Journal, 2023)
Background: Persistent diarrhea is a known cause of mortality, morbidity, and malnutrition in developing countries. With recent improvement of rehydration therapy death due to acute diarrhea has been reduced. Though persistent diarrhea accounts for 2-20% of total diarrhea cases, it accounts for 23-62% of all diarrhea related deaths. Objective: The study was done to identify the risk factors associated with persistent diarrhea in children below 5 years of age. Methods: This prospective observational study was conducted in the department of Pediatric Gastroenterology, Hepatology and Nutrition of Dhaka Shishu hospital from July 2019 to June 2020. It included 50 children with persistent diarrhea age between 1 month to <5 years. Detailed history, examination and appropriate investigations were done for all children. Crude odd ratio was calculated for each risk factor by univariate analysis and adjusted odds ratio was calculated by multivariate logistic regression. Results: Most of the children (52%) were under the age of 6 months to 1 year. Male (84%) were more affected than female (16%). Acute malnutrition was observed in 44% cases; among them severe acute malnutrition was in 40% cases. Unsafe drinking water, severe acute malnutrition, diarrhea within past 2 months, bottle feeding, persistent of dehydration more than 24 hours, feeding of cow’s milk, lack of exclusive breast feeding, prior antibiotic used, UTI, LRTI were statistically significant risk factors by univariate analysis. Unsafe drinking water (OR-1.6; 95% CI- 0.27- 2.78), severe acute malnutrition (OR-1.92; 95% CI-0.64 - 5.72), Feeding of cow’s milk (OR-3.90; 95% CI- 1.21- 12.49), lack of exclusive breastfeeding (OR-5.77; 95% CI- 1.44- 23.10), irrational use of antibiotics (OR-3.37; 95% CI- 1.01- 11.38), LRTI (OR-1.16; 95% CI- 0.49- 1.53) were found to be independent risk factors by multivariate logistic regression analysis. Conclusions: The results of this study concluded that use of unsafe drinking water, severe acute malnutrition, feeding of cow’s milk, lack of exclusive breastfeeding, irrational use of antibiotics are significant risk factors for the incidence of diarrhea in the present study population. Northern International Medical College Journal Vol. 12 No.2 Jan 2021, Page 539-543